2019
DOI: 10.1038/s41598-019-48034-2
|View full text |Cite
|
Sign up to set email alerts
|

De novo regulation of RD3 synthesis in residual neuroblastoma cells after intensive multi-modal clinical therapy harmonizes disease evolution

Abstract: Most high-risk neuroblastomas that initially respond to therapy will ultimately relapse. Currently, no curative treatment is available. Acquired genetic/molecular rearrangement in therapy-resistant cells contributes to tumor relapse. Recently, we identified significant RD3 loss in progressive disease (PD) and defined its association with advanced disease-stage and poor clinical outcomes. Here, we investigated whether RD3 loss is an acquired process in cells that survive intensive multi-modal clinical therapy (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Trigger events that up-or downregulate RD3 levels apparently facilitate protein or cell dysfunction. For example, previous work showed that RD3 is downregulated or lost in neuroblastoma cells that remained resistant to multi-modal clinical therapy ( Somasundaram et al, 2019 ). Furthermore, a previous study on the gene expression pattern in the rd3 mouse, an animal model of congenital blindness with low or no rd3 expression, reported that more than 1,000 genes are differentially regulated ( Cheng and Molday, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Trigger events that up-or downregulate RD3 levels apparently facilitate protein or cell dysfunction. For example, previous work showed that RD3 is downregulated or lost in neuroblastoma cells that remained resistant to multi-modal clinical therapy ( Somasundaram et al, 2019 ). Furthermore, a previous study on the gene expression pattern in the rd3 mouse, an animal model of congenital blindness with low or no rd3 expression, reported that more than 1,000 genes are differentially regulated ( Cheng and Molday, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…The same authors further showed that RD3 loss in a mouse model correlates with aggressive neuroblastoma cancer. More recently, Somasundaram et al (2019) found significant loss of RD3 expression on the transcript and protein level in patient derived tumor cells that survived intensive multi-modal clinical therapy. The authors conclude that transcriptional dysregulation might account for RD3 expression loss associated with advanced disease stage and low survival rate.…”
Section: Introductionmentioning
confidence: 99%
“…For this, human IMR-32 cells (i) exposed to mock-IR, (ii) RT (2Gy), (iii) PMA, (iv) after ectopic expression of p50/p65, (v) treated with GM6001 and exposed to RT, (vi) treated with aprotinin and exposed to RT, and (vii) transfected with ΔIkB and exposed to RT were collected 24 h post-RT. CMA construction, sectioning, and IHC were performed in our Tissue Pathology Core of the Stephenson Cancer Center following standard protocols, as described in our earlier work (Somasundaram et al 2019). Appropriate histology controls (H&E) and negative controls with no primary antibody were examined in parallel.…”
Section: Cell-microarray Construction and Immunohistochemistrymentioning
confidence: 99%
“…Consistently, global efforts were focused on identifying lead therapeutic deliverables that could target activated MMP9 signaling in NB (Li et al 2020;Xu et al 2019;Farabegoli et al 2018). Conversely, studies from our lab and others have showed therapeutic pressure-associated acquired molecular rearrangements, clonal selection, and cellular function, leading to drug resistance, NB evolution, and poor outcomes (Somasundaram et al 2019;Aravindan et al 2013b). For instance, therapeutic pressure has been shown to enhance tumor dissemination by facilitating MMP9 expression and metastatic niche (Zenitani et al 2018).…”
Section: Introductionmentioning
confidence: 95%